Managing moods: Media, politicians, and anxiety over public debate - Koivunen Anu (Routledge, 2022)
The notion of interregnum captures a mood: a sense of change and an anxiety regarding what will come and when. Interregnum is a state of waiting and anticipating, as it, in the Gramscian sense, denotes a period that lies between an old, declining system and an emerging new one. The 2010s entailed recurrent debates regarding debates, with a special focus on the tone and the attitudes of the participants. The metaphor captured and gave expression to media distrust, which in the 2010s became a topic of public discussion both in Sweden and in Finland. In Sweden, the ‘corridor of opinion’ metaphor demonstrated the power of social media to challenge the agenda and news values of professional journalism. In Finland, the centenary of 1918 served as a frame for discussions of where extreme polarisation and hate in the public sphere may lead, thus drawing from and adding to a rich narrative legacy, given the centrality of 1918 for the Finnish national imagination.
The Nordic Economic, Social and Political Model: Challenges in the 21st Century